Monetary base controllability after an exit from quantitative easing - Atsushi Tanaka (Journal of Central Banking Theory and Practice, 2020)
This study examines the problem that a central bank may face after exiting a monetary quantitative easing policy. It develops a simple dynamic optimization model of a central bank, which finds that if the bank needs to absorb a substantial amount of excess reserves when exiting, the monetary base may become uncontrollable. In this case, the bank has no option but to increase the monetary base by more than the target amount, which leads to an undesirable money supply expansion and, ultimately, to inflation pressures. The model shows the condition when a central bank faces such a challenging situation.
Keywords: E52; E58; 330; central bank; monetary base; quantitative easing; exit strategy; solvency